(untitled) (Quinto Sol, 2015)
The human resource training and knowledge generation adapted to the operating conditions of the various regional productions in Argentina, occupied the attention of experts from the Department of Agriculture, agrarian entities, political and educational sectors, since the early twentieth century. It did not escape this interest a concern about women and farm home. The aim of this paper is to analyze, in this context, the first decades of the “Ramón Santamarina” Farm School of Tandil, an establishment with a rich institutional history that housed the first school of farm home, soon transformed into a farm school and specialized in dairy industry. The transit to the farm household to the preparation of cheese masters, under productivist orientation of schools in the educational proposal of the Department of Agriculture, the social subjects involved, specialization in dairy and its results, are some of the issues discussed, as part of an educational agrarian project not only as a source of labor associated with specific agricultural industries, but also –and perhaps more than anything– as irradiators of that kind of teaching towards the community.